2018
DOI: 10.1007/978-3-319-93803-5_22
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of the Visibility of Latin American Universities and Their Impact on the Ranking Web

Abstract: The study analyzes the factors that contribute to the technical efficiency of the visibility of the universities included in the Top100 of the Latin American Universities Ranking Web published by Webometrics database in January, 2017. Data Envelopment Analysis (DEA) was used to calculate the contributions of input variables to efficiency. As data sources for inputs, the study considers the academic data published on the web of each university, the content and profiles displayed from Google Scholar (GS), data b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…The proposed method shows the best lowest clustering results and outperforms in a few prior researches [20], [21] and [22]. As indicated in Table 7, all existing methods have their complexity using evolutionary strategy automatic clustering methods for determining the number of clusters automatically in k-means, while the proposed method uses technical-statistical control for problem-solving of ACDE as an automatic clustering strategy for finding the optimal number of clusters in k-means method.…”
Section: Data Transformation Stagementioning
confidence: 91%
“…The proposed method shows the best lowest clustering results and outperforms in a few prior researches [20], [21] and [22]. As indicated in Table 7, all existing methods have their complexity using evolutionary strategy automatic clustering methods for determining the number of clusters automatically in k-means, while the proposed method uses technical-statistical control for problem-solving of ACDE as an automatic clustering strategy for finding the optimal number of clusters in k-means method.…”
Section: Data Transformation Stagementioning
confidence: 91%
“…Selama satu dekade pembahasan Webometric terus meningkat khususnya pembahasan mengenai pengukuran dari setiap indikator dalam Webometric seperti, Presence (P), Visibility (V), Transparency (T), serta Excellence (E). Seperti dalam penelitian [12]- [16], peningkatan Webometric lebih ditekankan pada aspek Visibility dan Transparency. Pada [12], menunjukan bahwa peningkatan visibility melalui publikasi data akademis pada website universitas serta konten dan profil yang ditampilkan pada Google Scholar (GS).…”
Section: Penelitian Terkaitunclassified
“…Seperti dalam penelitian [12]- [16], peningkatan Webometric lebih ditekankan pada aspek Visibility dan Transparency. Pada [12], menunjukan bahwa peningkatan visibility melalui publikasi data akademis pada website universitas serta konten dan profil yang ditampilkan pada Google Scholar (GS). Selain memanfaatkan GS, [12] juga menyebutkan bahwa penggunaan sosial media yang bersifat scientific network seperti ResearchGate ataupun media sosial biasa seperti Facebook, Twitter dan Instagram terbukti efektif meningkatkan visibility universitas di Amerika Latin.…”
Section: Penelitian Terkaitunclassified
“…Regarding the use of the Webometrics data, there are several researches that have already used them. For example, [7,8] compared different rankings like the Ranking of Shanghai, QS World University Ranking, SCimago Institutions Rankings SIR, and the Web Ranking of Universities-Webometrics, finding that the indicators associated with the research and institutional capacity stand out as common criteria in the reviewed evaluation methodologies. This research firstly states that Brazil occupies the first positions in the four rankings; and secondly, that there is a greater number of Latin American universities in QS (40%) and Webometrics (31%), while in the other two rankings it does not exceed 8%.…”
Section: Introductionmentioning
confidence: 99%
“…For its part, [8] and [10], used the Data Envelopment Analysis (DEA) for processing the academic data published on the website of each university, the content and profiles shown in Google Scholar (GS), the data published by the university in ResearchGate as scientific network, and finally, the data of social networks such as the Twitter and Facebook accounts of the corresponding institutions. The authors found that the postgraduate offer, visibility in GS, and the use of scientific and social networks contribute favorably to the web positioning of Latin American universities.…”
Section: Introductionmentioning
confidence: 99%